Impact of domestic public debt on financial development and economic growth in Malaysia - Mok, Wei Mun (2014)
Government interventions through fiscal policy are important to promote growth. In a nutshell, economic growth cannot be developed without government spending. Unfortunately, government tends to borrow from internal and external sources to finance budget deficit when additional government spending is unable to meet the tax revenue. Nowadays, the issue of higher public debt in Malaysia has received an attention from policy makers and economists. Given the abundance of liquidity and ample financial funds in the banking system, Malaysian government can continue borrow and mainly rely on domestic source to close the budgetary gap. Hence, the purpose of this study is to investigate the impact of domestic public debt on financial development and economic growth in Malaysia. The sample period in this study covers the annual time series data from 1980 to 2010. By using Autoregressive Distributed Lag (ARDL) cointegration bound test, this study estimates long run and short run relationship among domestic pblic debt, financial development and economic growth in Malaysia. The empirical finding suggests that outstanding of domestic public debt does crowd out private investment and have a statistically negative impact on financial development during the occurrence of financial crisis. Meanwhile, the ARDL long run coefficient reveals that domestic public debt has an adverse impact on the level of economic growth during the estimate period. In conclusion, government needs to concern over the debt level in order to reduce the debt burden for future generations.